Distinguishing autotrophic and heterotrophic respiration based on diel oxygen change curves: revisiting Dr. Faustus. (10th December 2013) - Kosten, Sarian; Demars, Benoît O. L.; Moss, Brian
Summary In his paper 'Climate change, nutrient pollution and the bargain of Dr. Faustus', Moss (Freshwater Biology, 55, 2010, 175) described the interacting and mutually reinforcing effects of climate change and nutrient pollution on aquatic ecosystems. Among other things, Moss (Freshwater Biology, 55, 2010, 175) proposed a simple method for determining autotrophic and heterotrophic respiration rates (Ra and Rh) based on the diel oxygen change technique. Here, we show that one of the assumptions on which the method is based is flawed and that Ra and Rh cannot be derived mathematically from diel oxygen change curves.